Highly efficient nanofocusing based on a T-shape micro-slit surrounded with multi-slits - Chen, Jianjun; Chen Wang; Guowei Lu; Wenqiang Li; Xiao, Jinghua; Qihuang Gong (OPTICS EXPRESS, 2012)
Highly efficient plasmonic nanofocusing is proposed and demonstrated in a T-shape micro-slit surrounded by multi-slits. The nanofocusing phenomenon is achieved based on the multimode interference in the micro-slit, the constructive interference in the T-shape slit, and also the multiple-beam interference of the light radiated from the multi-slits and the transmitted light from the T-shape micro-slit. Because of the large illumination areas of the incident light on the wide slit aperture in the proposed structure, a large amount of light can pass through the wide slit. This leads to a highly efficient nanofocusing. Meanwhile, the wide slit means easy fabrication. In the experiment, the focusing phenomenon in the proposed structure was successfully demonstrated with a scanning near-field optical microscopy (SNOM) technology. (C) 2012 Optical Society of America